Antidiscrimination education and the hidden curriculum. Word and picture - Jonczy-Adamska, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2014)
The article establishes the analysis of the findings outcomes executed by The Antidiscrimination Education Association (TEA) in frames of the project Significant Absence – on anti-discrimination education in the formal education system in Poland in terms of the occurrence of a hidden curriculum in context of passing contents regarding groups which are discriminated and excluded. The analysis was submitted to verbal and graphic content in polish handbooks, as well in what way the language carries biases and shapes the perception of different social groups.